Discrimination, domestic violence, abuse, and other adverse life events in people with epilepsy: Population‐based study to assess the burden of these events and their contribution to psychopathology. (16th September 2016) - Nimmo‐Smith, Victoria; Brugha, Traolach S.; Kerr, Michael P.; McManus, Sally; Rai, Dheeraj
Summary: Objective: To quantify the experience of discrimination, domestic violence, abuse, and other stressful life events in people with epilepsy in comparison with the general population and people with other chronic conditions. To assess whether any excess relative burden of these adversities could explain the higher rates of depression in people with epilepsy. Methods: The Adult Psychiatric Morbidity Survey 2007 used comprehensive interviews with 7, 403 individuals living in private residences in England. Doctor‐diagnosed epilepsy and other chronic conditions were established by self‐report. Discrimination, domestic violence, physical and sexual abuse, and other stressful life events were assessed using computerized self‐completion and a face‐to‐face interview, respectively. Results: People with epilepsy were sevenfold more likely to have reported experiencing discrimination due to health problems (adjusted odds ratio [OR] 7.1; 95% confidence interval [CI] 3.1–16.3), than the general population without epilepsy. This estimate was substantially greater in people with epilepsy than for people with other chronic conditions. People with epilepsy also had greater odds of experiencing domestic violence and sexual abuse than the general population, although these associations were also found in people with other chronic conditions. There was less evidence of an association between epilepsy and a history of physical abuse or having a greater burden of other stressful life events. In exploratory analyses, assuming they lie on the causal pathway, discrimination, domestic violence, and sexual abuse explained 42.7% of the total effect of the relationship between epilepsy and depression or anxiety disorders. Significance: People with epilepsy can face a range of psychosocial adversities and extensively report feeling discriminated against as compared to the general population. In addition, if confirmed in longitudinal studies, the results suggest that these psychosocial adversities may have a significant role in the development of psychiatric comorbidity and may be targets for future interventions.